Effect of Volumetric Energy Density and Part Height on the Material Properties of Low-Alloyed Steels Manufactured by Laser-Based Powder Bed Fusion of Metals - Bartels, Dominic; Novotny, Tobias; Albert, Moritz; Mohr, Andreas; van Soest, Frank; Hill, Horst; Merklein, Carsten; Schmidt, Michael (Advanced Engineering Materials, 2023)
The layer-by-layer manufacturing approach in laser powder bed fusion of metals (PBF-LB/M) leads to heat accumulation in the workpiece with increasing part heights. The effect of this heat accumulation on the resulting material properties has, however, only barely been studied for low-alloyed steels. The goal of this work is to analyze the influence of different PBF-LB/M-specific boundary conditions like varying part heights and volumetric energy densities (VED) on the resulting material properties. It isfound that lower part regions possess similar hardness (380–410 HV1) and retained austenite values (7%–8%), independent of the applied VED. Higher energy inputs lead to higher retained austenite contents of up to 20% due to an incomplete transformation upon cooling. This rise in retained austenite content is also linked to a decreased material hardness down to 320 HV1. In higher part regions, this effect is reversed as the retained austenite content starts to decrease for the highest investigated VED. This is caused by the in situ preheating temperatures caused by heat accumulation, which favor a bainitic transformation. The part height-specific properties indicate that the microstructure formation forms through a continuous transformation in lower part regions and through an isothermal transformation in higher regions.
CRIS-Team Scopus Importer:2023-09-29
Keywords: additive manufacturing; Bainidur AM; laser-based powder bed fusion of metals; low-alloyed steel; material properties; microstructure formation